DEVELOPING A SCIENCE TEACHING MODULE BASED ON DIFFERENTIATED LEARNING IN ELEMENTARY SCHOOLS - Aliani; Mulabbiyah; Alwan Mahsul (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2025)
The purpose of this study is to develop a science and natural sciences (IPAS) teaching module based on differentiated learning on the topic